Practitioners’ perceptions of acceptability of a question prompt list about palliative care for advance care planning with people living with dementia and their family caregivers: a mixed-methods evaluation study - Raymond TCM Koopmans; Jenny T van der Steen; Josephine Clayton; Wilco P Achterberg; Yvette M van der Linden; Genevieve Thompson; Sten Heck; Carla CM Juffermans; Mirjam Marjolein Garvelink (BMJ Open)
Objectives In oncology and palliative care, patient question prompt lists (QPLs) with sample questions for patient and family increased patients’ involvement in decision-making and improved outcomes if physicians actively endorsed asking questions. Therefore, we aim to evaluate practitioners’ perceptions of acceptability and possible use of a QPL about palliative and end-of-life care in dementia.Design Mixed-methods evaluation study of a QPL developed with family caregivers and experts comprising a survey and interviews with practitioners.Setting Two academic medical training centres for primary and long-term care in the Netherlands.Participants Practitioners (n=66; 73% woman; mean of 21 (SD 11) years of experience) who were mostly general practitioners and elderly care physicians.Outcomes The main survey outcome was acceptability measured with a 15–75 acceptability scale with ≥45 meaning ‘acceptable’.Results The survey response rate was 21% (66 of 320 participated). The QPL was regarded as acceptable (mean 51, SD 10) but 64% felt it was too long. Thirty-five per cent would want training to be able to answer the questions. Those who felt unable to answer (31%) found the QPL less acceptable (mean 46 vs 54 for others; p=0.015). We identified three themes from nine interviews: (1) enhancing conversations through discussing difficult topics, (2) proactively engaging in end-of-life conversations and (3) possible implementation.Conclusion Acceptability of the QPL was adequate, but physicians feeling confident to be able to address questions about end-of-life care is crucial when implementing it in practice, and may require training. To facilitate discussions of advance care planning and palliative care, families and persons with dementia should also be empowered to access the QPL themselves.